Preparation of methyl levulinate from fractionation of direct liquefied bamboo biomass. (15th September 2015) - Feng, Junfeng; Jiang, Jianchun; Xu, Junming; Yang, Zhongzhi; Wang, Kui; Guan, Qian; Chen, Shuigen
Highlights: Methyl levulinate was produced from bamboo by direct liquefied conversion. The yield of methyl levulinate can reach to 30.75 wt% using bamboo methanolysis. Models compounds were used to describe the reaction pathway of direct liquefaction. Abstract: One-step preparation of methyl levulinate from biomass was investigated. The process used was direct liquefaction under pressure in methanol using a 1 L autoclave. Bamboo, a lignocellulosic biomass, was liquefied using sulfuric acid in subcritical methanol. When sulfuric acid was used as the catalyst, a 30.75 wt% methyl levulinate yield could be obtained from bamboo at 200 °C after a reaction time of 120 min when the catalyst loading was 2.5 wt% per 60 g bamboo. In addition, microcrystalline cellulose, corn starch, methyl glucoside and glucose were selected as model compounds for the liquefaction reaction so that the biomass to methyl levulinate reaction pathway could be investigated. The results suggested that lignocellulosic biomass is a renewable material that can be used to produce a high value-added fuel additive (methyl levulinate) by the direct liquefaction under pressure reaction process.